Bacterial Growth and Protein Degradation in Different Fish Flesh Extracts and Casein Media - Philip, Rosamma; P., Lakshmanaperumalsamy (Fishery Technology, 2025)
The four bacterial strains tested showed considerable variations in the growth pattern and extent ofprotein degradation in fish, prawn and clam extract media and casein medium. During the first 12h of incubation, growth rate of all the strains were higher in prawn flesh broth compared to that in other media except for Pseudomonas sp.Ca 173. On prolonged incubation these bacteria did grow equally well in other media also. Generally, in all the media, protein degradation commenced on the third day and progressed rapidly.